2018
DOI: 10.1002/jsfa.9087
|View full text |Cite
|
Sign up to set email alerts
|

Control efficacy of Ca‐containing foliar fertilizers on bitter pit in bagged ‘Fuji’ apple and effects on the Ca and N contents of apple fruits and leaves

Abstract: Foliar fertilizer containing CaCl Ca(NO ) or Ca(HCOO) can be used at an early stage to control BP in apple and improve the quality of bagged apple fruits. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…The growth rates in fleshes were high than that in peels and leaves, indicating that the trimetallic complex can improve the accumulation of N in the fruit flesh. The results were inconsistent with the N contents regulated by inorganic calcium salt ( 45 ), demonstrating the promotion effect of MRPs to the accumulation of N content. However, the mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The growth rates in fleshes were high than that in peels and leaves, indicating that the trimetallic complex can improve the accumulation of N in the fruit flesh. The results were inconsistent with the N contents regulated by inorganic calcium salt ( 45 ), demonstrating the promotion effect of MRPs to the accumulation of N content. However, the mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 76%
“…Many studies have been carried out to study the spray effect of metal salts ( 35 37 ), metal oxides ( 38 , 39 ), and metal complexes ( 40 – 43 ) on plant growth. Ca sprays are more effective than soil applications at allocating and increasing the Ca content in the apple fruits and could help reduce the incidence of Ca-related disorders ( 44 , 45 ). Zn sprays enhance the fruit Zn content and result in the higher activities of carbohydrate metabolism-related enzymes, contributing to the accumulation of carbohydrates ( 46 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2016) demonstrated that the relationship between intracellular Ca concentration and tipburn in Brassica oleracea differed between genotypes and were correlated with differential expression of a number of transporter and stress response genes. In apple, Ca deficiency is called bitter bit, reflecting that the fruit skin develop pits and that brown spots appear on the skin and/or in flesh, resulting in a bitter taste (Buti et al, 2018;Yu XM et al, 2018). Calcium deficiency in carrot leads to cavity spot, characterised by oval necrotic spots developing into craters.…”
Section: Calcium Deficiency Symptoms Linked To Functional Propertiesmentioning
confidence: 99%
“…Foliar application of urea is a common practice in apple orchards, particularly in conditions unfavorable for soil fertilization. Moreover, low levels of nitrogen are often incorporated in preharvest foliar sprays which are used to improve fruit quality, delay fruit ripening, or decrease postharvest fruit decay [11]. However, the present study displays negative impacts of low-doses of urea applied several times during the apple cell enlargement stage in the final stages of fruit development.…”
Section: Discussionmentioning
confidence: 64%
“…This nutrient is added to the soil or applied in the form of foliar fertilizers. This measure is implemented several times throughout the season starting from late June until the final week before harvest with the aim of improving apple fruit firmness, shelf life, as well as preventing some storage disorders [9][10][11]. Moreover, low-level nitrogen fertilizers are added on-leaf to quickly alleviate sudden nutrient deficiencies as they are readily available to the plant [12].…”
Section: Introductionmentioning
confidence: 99%